A two-step sequential method for device-free localization using wireless sensor networks - Tingting Wang; Wendong Hua; Wei Ke (International Journal of Distributed Sensor Networks)
The device-free localization that locates an uncooperative target by analyzing its shadowing effect on wireless links in low-cost wireless sensor networks has become an attractive technique. Due to its ability of realizing localization without the need of equipping the target with any wireless device, device-free localization has lots of potential applications ranging from emergency rescue to patient monitoring. However, since the change of the received signal strength on links easily becomes unpredictable due to all kinds of dynamical factors, device-free localization is still a challenging problem. In this article, we propose a novel two-step sequential device-free localization method to enhance device-free localization performance. The sequential device-free localization first utilizes the geometric-based method to quickly obtain the coarse positioning result with low storage and computational requirements, and then exploits the location information of selected wireless nodes to improve the accuracy of the geometric-based localization result based on the optimization-based method, which ensures its robust performance. Experimental results in indoor and outdoor scenarios demonstrate the effectiveness and robustness of the proposed scheme.